The Prevalence and Predictors of Penile Pain in Men with Peyronie's Disease - Jose M. Flores, MD, MHA; Carolyn A. Salter, MD; Bruno Nascimento, MD; Jean-Etienne Terrier, MD, PhD; Hisanori Taniguchi, MD; Helen L. Bernie, DO, MPH; Eduardo Miranda, MD, PhD, FECSM; Lawrence Jenkins, MD; Elizabeth Schofield, MPH; John P. Mulhall, MD, MSc, FECSM (Sexual Medicine, 2021)
ABSTRACT: Introduction: Penile pain is one of the most stressful symptoms in men with Peyronie's disease (PD). Aim: To evaluate the prevalence, clinical presentation and risk factors associated with penile pain in men with PD as well as to assess the psychosocial impact. Methods: We revised our institution's database of men diagnosed with PD. The information collected included penile pain assessments, and the scores of the PD Questionnaire (PDQ), Self-Esteem and Relationship Questionnaire (SEAR) and Center for Epidemiologic Studies Depression Scale Questionnaire (CES-D). Descriptive and comparative statistics were used. Logistic regression analyses were performed to evaluate predictive factors associated with penile pain. Main outcome measures: Penile pain descriptive assessment and factors associated with penile pain in men with PD. Comparison of SEAR, CES-D and PDQ domain scores of men with and without penile pain. Results: 431 men with PD were included for this analysis with a mean age of 55.9 years. Penile pain was reported by 36.7%; 65.2% of those had painful erection, 7% pain with flaccid state only, and 20% in both stages. The median pain severity was 3 with erection and 1 with flaccid stage. After adjusted logistic regression analyses, advanced age was associated with less pain (OR 0.94, P ≤ 0.001). Men with penile pain had no significant difference in CES-D and SEAR mean scores compared to men without penile pain. The PDQ scores for the physical/psychological symptoms domain and the bother domain were significantly higher in men with penile pain (12 vs 8.7; P < 0.01 and 9 vs 7.1; P < 0.01 respectively). Men with penile pain had a higher rate of clinically significant bother scores than men without penile pain (52% vs 35%, P ≤ 0.001). Conclusion: Penile pain is common in men with PD. It was more common in young men and was associated with physical and psychological bothers in this population.Flores JM, Salter CA, Nascimento B, et al. The Prevalence and Predictors of Penile Pain in Men with Peyronie's Disease. Sex Med 2021;9:100398.